(untitled) (Педагогіка вищої та середньої школи, 2008)
The article concerns the epistemological study of knowledge as the subjective unity viewed by native and abroad investigations. The epistemology as a branch of as well as the manifestation of subjective form of knowledge and knowing are under discussion. Main directions of the abroad epistemological studies are analyzed.